2022
DOI: 10.3389/fmicb.2022.904358
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Pathogenic Mechanism of Covert Mortality Nodavirus Infection in Penaeus vannamei

Abstract: Viral covert mortality disease (VCMD), also known as running mortality syndrome (RMS), is caused by covert mortality nodavirus (CMNV) and has impacted the shrimp farming industry in Asia and Latin America in recent years. The pathogenic mechanism of CMNV infecting Penaeus vannamei was investigated in this study. In the naturally infected shrimp, histopathological and in situ hybridization (ISH) analysis verified that CMNV infection and severe cellar structural damage occurred in almost all cells of the ommatid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that CMNV possesses the ability to cause several types of pathology to the tissues and organs of prominent farmed crustaceans [57,58]. Moreover, CMNV has exhibited its capacity to surpass species barriers and infect a wide array of cultivated and wild fish species, obtained from various habitats including prawn ponds or drainage channels that have been impacted by CMNV [59,60]. This statement emphasizes the inherent capacity of CMNV to surpass taxonomic divisions, thus highlighting its ability to infect both vertebrate and invertebrate taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that CMNV possesses the ability to cause several types of pathology to the tissues and organs of prominent farmed crustaceans [57,58]. Moreover, CMNV has exhibited its capacity to surpass species barriers and infect a wide array of cultivated and wild fish species, obtained from various habitats including prawn ponds or drainage channels that have been impacted by CMNV [59,60]. This statement emphasizes the inherent capacity of CMNV to surpass taxonomic divisions, thus highlighting its ability to infect both vertebrate and invertebrate taxa.…”
Section: Discussionmentioning
confidence: 99%